2013
DOI: 10.1371/journal.pone.0067412
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Application of gp140 Encoding DNA Polyplexes to Different Tissues Results in Altered Immunological Outcomes in Mice

Abstract: Increasing evidence suggests that mucosally targeted vaccines will enhance local humoral and cellular responses whilst still eliciting systemic immunity. We therefore investigated the capacity of nasal, sublingual or vaginal delivery of DNA-PEI polyplexes to prime immune responses prior to mucosal protein boost vaccination. Using a plasmid expressing the model antigen HIV CN54gp140 we show that each of these mucosal surfaces were permissive for DNA priming and production of antigen-specific antibody responses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…To assess gamma interferon (IFN-␥) T cell responses, cultures of lymphocytes from spleens were prepared as described previously (18,19 Immunoglobulin ELISA and avidity assay. A quantitative immunoglobulin enzyme-linked immunosorbent assay (ELISA) protocol described previously (18,19) was followed. Briefly, 5 g/ml gp140-coated ELISA plates were blocked with 200 l/well 1% bovine serum albumin and 0.05% phosphate-buffered saline (PBS)-Tween 20 (PBST).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess gamma interferon (IFN-␥) T cell responses, cultures of lymphocytes from spleens were prepared as described previously (18,19 Immunoglobulin ELISA and avidity assay. A quantitative immunoglobulin enzyme-linked immunosorbent assay (ELISA) protocol described previously (18,19) was followed. Briefly, 5 g/ml gp140-coated ELISA plates were blocked with 200 l/well 1% bovine serum albumin and 0.05% phosphate-buffered saline (PBS)-Tween 20 (PBST).…”
Section: Methodsmentioning
confidence: 99%
“…IFN-␥ enzyme-linked immunosorbent spot (ELISpot) assays (Mabtech, United Kingdom) were carried out on splenocytes per the manufacturer's instructions and as described previously (18,19). Plates were blocked for 30 min using complete RPMI before addition of 5 ϫ 10 6 cells/ml.…”
Section: Methodsmentioning
confidence: 99%
“…In subsequent i.n. challenge with live murine-adapted X-31 (H3N2) influenza virus, statistically significant protection was confirmed (Mann et al, 2013). …”
Section: Oral Dna Vaccinationmentioning
confidence: 91%
“…To test this, we evaluated whether Tf-HA could boost responses after sublingual priming with a DNA vaccine expressing HA. In previous studies, we have demonstrated that HA delivered as DNA can induce a potent immune response [14] and have demonstrated that mucosal DNA delivery can be potentiated by PEI [10]. Mice were immunized three times with DNA sublingually and subsequently boosted with HA alone or Tf-HA.…”
Section: Conjugation Of Transferrin To Haemagglutinin Significantly Ementioning
confidence: 99%
“…The sublingual route of oral vaccine delivery has long been investigated due to its numerous antigen sampling points and organized lymphoid structures [7][8][9][10]. However, it has had limited success in larger animals [11] and therefore strategies to boost efficacy are required.…”
Section: Introductionmentioning
confidence: 99%